IMPACT OF INFLUENCER MARKETING ON PURCHASE INTENTION OF CUSTOMERS - Dr. Minakshi Sati, Dr. Neelam Sharma, Dr. Indu Rani, Romita Modi, Shubham Mishra (Chelonian Research Foundation, 2023)
Influencer marketing on social media has drawn a lot of attention recently. The development of parasocial relationships (PSRs) between influencers and followers has been the subject of numerous research. Despite the abundance of PSR studies, PSR has not been frequently weighed against other popular relationship marketing frameworks. In order to determine the proportional weight of the PSR, this study created a research model based on the theory of persuasion. Three characterizations (trustworthiness, perceived expertise, and PSR) and three personal traits (attitude homophily, physical attractivness and social attractiveness) were taken into consideration by the study as determinants of purchase intention. Information was gathered via a survey of participants who purchased goods or services following the influencer on YouTube. The study discovered that PSR was significantly correlated with the three personal traits and that it had a significantly positive impact on purchase intentions when compared to other characterizations. This paper discusses the factors that impacts on purchase intention of an individual while purchasing products or services recommended by the influencers.